A case of idiopathic edema after opioid abuse cessation: can failed aldosterone escape be implicated? - Ratnam, Ashutosh; Sashindran, V. K.; Kanwar, Anup (International Journal of Basic & Clinical Pharmacology, 2019)
Edema is a recognized complication of ongoing heavy opioid use, regardless of the means of delivery or the specifics of the drug in question. The mechanism responsible remains incompletely understood. Hypotheses currently offered include increased Anti-Diuretic Hormone (ADH) secretion, histamine-mediated permeability changes, independent opioid-receptor mediated fluid retention and an exacerbation of pre-existing vascular compromise. Authors report a case of a 39yr old lady in whom edema emerged 7 months after cessation of opioid abuse. All secondary causes of edema were excluded by an exhaustive battery of investigations. The edema failed to recede with loop diuretics, and resolved only on institution of spironolactone, on which she maintained improvement. This case study reinforces hypotheses of ADH likely mediating opioid associated edema and suggests that aldosterone receptor antagonists are probably a superior class of drugs in opioid-associated edema. It also suggests that the physiological changes caused by opioid use that are responsible for edema are likely stable and persist well beyond the period of actual use. Reformed opioid abusers who never received OST are a huge population whose unique physiological status is likely to yield valuable insights into not just the pathology of opioid-abuse related edema, but the pathology of opioid use as a whole.